Biomechanical impact testing of synthetic versus human cadaveric tibias for predicting injury risk during pedestrian-vehicle collisions. (17th February 2020) - Cameron, Muir W.; Schemitsch, Emil H.; Zdero, Radovan; Quenneville, Cheryl E.
Abstract: Objective: The tibia is the most commonly fractured long bone in a pedestrian-vehicle collision. The standard injury assessment tool is the "legform, " a device that mimics the human lower limb under impact loads. These devices are designed to identify the impact load that will cause the onset of injury, rather than replicate the type and severity of fracture. Thus, this study is the first to determine if composite tibias made by Sawbones (Pacific Research Labs, Vashon, WA, USA) designed for orthopedic biomechanics research, could also potentially be used for traffic safety research by simulating both the damage tolerance of human cadaveric tibias for peak force and bending moment and the fracture patterns themselves, thereby more accurately predicting injury type during real-world pedestrian-vehicle collisions. Methods: Synthetic tibias (n = 6) and human cadaveric tibias (n = 6) were impacted at midshaft at 8.3 m/s (i.e., 30 km/h) under 3-point bending using a pneumatic impacting apparatus. Fracture force, bending moment, and fracture patterns were compared between the two groups, and Weibull survivability curves generated for force and moment results, to identify injury risk thresholds. Results: There was no difference for synthetic vs. cadaveric tibias regarding impact force (4271+/-938 N vs. 4889+/-993 N, p = 0.44) or bending moment at fracture (275+/-64 Nm vs. 302+/-107 Nm, p = 0.69). Force-time curves for all tibias were similar in shape based on the first three Principal Components (p > 0.14). Weibull survivability curves had differences in shape and in the 10% risk of fracture limits, with force thresholds of 2873 N for the synthetic vs. 3386 N for the cadaveric, and bending moment limits of 180 Nm for the synthetic compared to 157 Nm for the cadaveric. All fracture patterns were clinically realistic, but not consistent between groups. The coefficient of variation for synthetic tibias was >0.2 for both peak force and bending moment, which precludes their use as a reproducible test surrogate for injury prediction. Conclusions: Synthetic composite tibias offer the potential for developing a frangible test surrogate, and matched cadaveric response in several respects. However, the repeatability was not high enough for them to be used in their present form for injury prediction.